César Vallejo: la prosa poética de algunos artículos periodísticos - Huárag, Eduardo (2021)
Study of some journalistic chronicles (1924-1929) by César Vallejo that, after some substantive modifications, end up turning into poetic prose. Certainly, there is a sort of communicating vessel between the chronicle and the literary story. The same topic and incident are addressed, and while in one case journalistic information prevails, in the other the verbal expression is modified and subjected to the demands of the literary story. This study also adds the analysis of two poetic prose texts that have no precedent in journalistic articles. As will be seen, it is a search process in which the poet and narrator defines his style, his prose and his ideological ideology.